An examination of innovative consumers' playfulness on their pre-ordering behavior. Issue 3 (8th May 2017) - Byun, Kyung-Ah; Dass, Mayukh; Kumar, Piyush; Kim, Junghwan
Abstract : Purpose: The purpose of this paper is to examine the role of playfulness on innovative consumers' pre-order behavior for new products. Design/methodology/approach: Drawing upon self-congruity theory and early adoption literature, the effects of playfulness and innovativeness on pre-order behavior and the role of self-congruity are tested using four experimental studies that are analyzed using generalized linear model (GLM) and structural equation modeling. Findings: Results indicate that playfulness amplifies the advance-purchasing propensity, especially when the pre-launch information cues come from a credible source. Originality/value: This paper refines playfulness measurement scales and proposes how both enjoyment- and creativity-based playfulness amplify the purchase intention among innovative consumers. The results assist product managers in developing advanced marketing plans before a new product is launched.